Oil in the Context of the U.S. Energy Security - Varjan, Milan; Čajka, Radek, 1983-; Taušer, Josef; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2015)
Oil is the world's most valuable energy resource without which no highly industrialized society can survive and whose availability must be guaranteed, if necessary by military. This thesis contributes to supporting this reality by analyzing the role of oil in the process of providing for the energy security in the United States. The framework introduces the concept of oil in the economy and its position in providing for the energy security.
Vedoucí práce: Radek Čajka
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses